Self-assembled xanthate-transition metal polyether macrocycles and cryptands - Beer, P; Cowley, A; Jeffery, J; Paul, R; Wong, W (2003)
The synthesis of novel dinuclear nickel(II)-xanthate polyether macrocycles and dinuclear cobalt(III)-xanthate polyether cryptands is reported. The assemblies have been characterised by a range of spectroscopic techniques and in one case by X-ray crystal structure determination. Electrospray mass spectrometry provided evidence that the dinuclear nickel(II)-xanthate macrocycles form adducts with Group I metal cations and methyl viologen (MV2+). The dinuclear cobalt(III)-xanthate cryptands also form adducts with Group I metal cations but did not interact with MV2+. © 2003 Elsevier Science Ltd. All rights reserved.